O LongForm como alternativa ao microconteúdo na produção de materiais didáticos para m-learning - Gomes, Nicole de Santana (2018)
The research proposes the comparative critical analysis of production models of materials used for didactic purposes in Distance Education (EaD) mediated by mobile technologies when confronting the formats Microcontevida and LongForm. Microcontent is the most commonly found in the EaD online, being composed by small and fragmented information units; while LongForm presents itself as an emerging trend of content production, built through in-depth and extensive information, constituting an alternative model to what prevails today. The methodological strategy is to compare the two formats from the perception of students of Higher Education on the experience of using representative examples of these materials. The relevance of the research lies in the search for alternatives for the production of didactic material that do not simplify the contents and do not harm the educational process, in view of the progress of EaD in Brazil and in the world, and the tendency of the use of mobile communication devices in the education. The research is based on the application of activity that involved study through materials elaborated in the two formats and evaluation formulated according to the characteristics of these formats, as well as the analysis of the data referring to the preferences of participants' use. Participated in 67 undergraduate courses offered at a university in the interior of Minas Gerais. As a result, it was found that the Microconteudo was efficient in the process of learning construction, since the students navigated, on a regular basis, the informational micro-units offered; it was possible to perceive that this model constitutes, therefore, an ideal format for smaller materials, in both size and content density. It was concluded that LongForm is a format that can extend its borders to be used not only in journalism, but also in distance education, as it has proved to be suitable for addressing complex, dense content that uses multimedia elements to elucidate information, constituting an appropriate support for the studies.